Experience and clinical efficacy of gut‐directed hypnotherapy in an Asian population with refractory irritable bowel syndrome. Issue 7 (19th May 2022) - Sasegbon, Ayodele; Hasan, Syed S; Whorwell, Peter J; Vasant, Dipesh H
Abstract: Background and Aim: Recent studies have highlighted the high worldwide prevalence of irritable bowel syndrome (IBS) and disparities in its management between ethnic groups. For instance, gut‐directed hypnotherapy (GDH), one of the most effective evidence‐based treatments for IBS, is not recommended in Asian countries partly due to lack of population‐specific outcome data. In this context, we evaluated the outcomes of GDH in an Asian population. Methods: Consecutive British Asian patients with refractory IBS who received 12‐sessions of GDH using the Manchester protocol were included. Patients were treated by a team including a therapist able to speak several Asian languages. All patients prospectively completed the following questionnaires before and after GDH: IBS symptom severity score (IBS‐SSS), hospital anxiety and depression scale (HADS), non‐colonic symptom score, and the quality‐of‐life (QOL) score. The primary outcome measure was response to GDH defined by ≥50‐point reduction in IBS‐SSS. Pre‐ and post‐treatment data were compared statistically. Results: Forty‐four Asian patients with IBS (age 49 ± 13 years; 29 [66%] female; baseline IBS‐SSS: 332.8 ± 94.6) completed GDH. Overall, 37 of 44 (84%) achieved a ≥50‐point reduction in IBS‐SSS and 25 of 44 (57%) achieved ≥30% reduction in abdominal pain scores. Following GDH, there were also significant mean improvements in IBS‐SSS (−132.1, P  < 0.0001), non‐colonic symptom score ( P  < 0.0001), QOL score ( P  < 0.0001), HADS‐anxiety ( P  < 0.0001), and HADS‐depression ( P  < 0.0001), compared with baseline. Conclusion: Regardless of the ethnicity of the therapist, GDH was highly effective with similar response rates to outcomes in other IBS populations, supporting the development of GDH in Asian countries. Abstract : This study suggests that hypnotherapy is a highly effective treatment approach in an Asian population with refractory irritable bowel syndrome. Hypnotherapy significantly improves gastrointestinal, extra‐intestinal, psychological symptoms, and quality of life. These data have highlighted the need for developing hypnotherapy services and population‐specific clinical studies to confirm these findings in Asian countries.